Combined application of humic acid and arbuscular mycorrhizal fungi regulates microbial community dynamics and enhances mercury-resistant genes in mercury-polluted paddy soil. (1st October 2022) - Yang, Tianxue; Liu, Liang; Li, Meng
Abstract: Humic acid and arbuscular mycorrhizal fungi (AMF) in mercury (Hg) polluted paddy soil may individually induce changes of microbial community, which is essential to mercury (Hg) resistance. However, little is known regrading the effect of the combination of humic acid and AMF on the microbial community assembly in different rhizospheric zones along the growth stages of rice. In the present study, a pot experiment was conducted by applying humic acid alone (HA) or in combination with AMF (HAAM) to examine the changes in microbial community and mer A/B gene abundance. The results showed that growth stage and amendment of humic acid and AMF had important influence on the richness, diversity, and composition of bacterial and fungal communities. By contrast, a very limited rhizospheric effect on the microbial community richness and diversity was found. Diverse soil properties were responsible for the changes of bacteria, fungi, and AMF, respectively. Dissolved organic carbon (DOC) and redox potential (Eh) strongly affected fungi community, while the shift in bacterial community was mainly attributed to DOC ( P  < 0.05), pH ( P  < 0.05), and water-soluble Hg (WHg) ( P  < 0.05). The HAAM treatment promoted the diversity of AMF (14.0 ± 8.3 of Ace index, 15.6 ± 5.4 of Chao index) benefited from the input of organic carbon and total nitrogen (TN) along with the addition of humic acid and AMF inocula into soils. In addition, the HAAM treatment induced a much higher abundance of mer A (6.19 × 10 8 ±2.32 × 10 8 copy g −1 ) and mer B (0.52 × 10 7 ±0.09 × 10 7 copy g −1 ) genes than the HA treatment alone, suggesting the importance of a combined amendment of humic acid and AMF inocula. Our findings demonstrate the regulation of soil microbial community and the improvement of Hg-resistant genes and microbes under the combined application of humic acid and AMF with the objective to the Hg pollution control in the paddy field.